2016
DOI: 10.1103/physrevx.6.031022
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Spin-Orbit-Coupled Degenerate Dipolar Fermi Gas

Abstract: We describe the creation of a long-lived spin-orbit-coupled gas of quantum degenerate atoms using the most magnetic fermionic element, dysprosium. Spin-orbit-coupling arises from a synthetic gauge field created by the adiabatic following of degenerate dressed states comprised of optically coupled components of an atomic spin. Because of dysprosium's large electronic orbital angular momentum and large magnetic moment, the lifetime of the gas is limited not by spontaneous emission from the light-matter coupling,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
148
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 74 publications
10
148
0
Order By: Relevance
“…Most experimental studies of spin-orbit coupling with ultracold atoms used two hyperfine ground states coupled by a two-photon Raman spin flip process [9][10][11][21][22][23][24] . All previous studies with bosons used 87 Rb [9][10][11] .…”
mentioning
confidence: 99%
“…Most experimental studies of spin-orbit coupling with ultracold atoms used two hyperfine ground states coupled by a two-photon Raman spin flip process [9][10][11][21][22][23][24] . All previous studies with bosons used 87 Rb [9][10][11] .…”
mentioning
confidence: 99%
“…In ultracold experiments, it is necessary to characterize the photon-scattering rate, as it provokes heating of the sample, and trap losses [44]. Beyond trapping itself, the real part of the vector and tensor DDPs are also necessary to determine the Ramancoupling strengths between different Zeeman sublevels, which was proposed for the implementation of synthetic gauge fields [17,18]. In our previous works on Er [45] and Dy [46], we have shown that, far from resonant fre-quencies, the ac-Stark shift only weakly depends on the field polarization and atomic Zeeman sublevel, despite the absence of spherical symmetry in the 4f -electron wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…An optical lattice clock scheme [23] was proposed to suppress the heatings issue and generate a 2d SOC in an optical lattice. Most recently, by using the most magnetic fermionic element dysprosium to eliminate the heating due to the spontaneous emission, the authors in [25] created a long-lived SOC gas of quantum degenerate atoms. The long lifetime of this weakly interacting SOC degenerate Fermi gas will facilitate the experimental study of quantum many-body phenomena manifest at longer time scales, So the novel phases and phase transitions in figures 1 and 2 are ready to be explored in near future cold atom experiments.…”
Section: Experimental Realizations and Detections In The Original Andmentioning
confidence: 99%
“…Recently, there are also some advances [21][22][23][24] to overcome this difficulty in generating 2D Rashba SOC for cold atoms in both continuum and optical lattices and also in a Zeeman field. Most recently, a long-lived SOC gas of the high magnetic fermionic element dysprosium to eliminate the heating due to the spontaneous emission, has been created in [25]. In view of these recent experimental advances, novel superfluid or magnetic phenomena due to the interplay among tunable interactions, SOC and a Zeeman field are ready to be investigated in near future experiments on both fermion and spinor BEC.…”
Section: Introductionmentioning
confidence: 99%